2022
DOI: 10.1016/j.psj.2021.101623
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and safety evaluation of L-glutamic acid, N,N-diacetic acid as a feed additive in broiler diets

Abstract: The novel chelator, L-glutamic acid, N,N-diacetic acid ( GLDA ) can be used as a dietary ingredient to safely reduce Zn supplementation in complete feed, without compromising the Zn status of farm animals. The objective of this study was to study dietary tolerance, bioaccumulation, and evaluate the safety of GLDA when supplemented in broiler diets at 0, 100, 300, 1000, 3,000, and 10,000 mg/kg. A total of 480 one-day-old Ross 308 male broilers were randomly allocated to 48 pens and fed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, researchers have found that the use of antibiotics has drawbacks, such as drug residues and bacterial resistance to antibiotics. Due to the low digestibility of zinc, high doses of ZnO in the feed leads to high zinc emission in feces of the livestock, thus causes the waste of resources and the environmental pollution ( 2 , 3 ). Many countries have phased out the use of colistin sulfate, olaquindox and high-dose ZnO as feed additives.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have found that the use of antibiotics has drawbacks, such as drug residues and bacterial resistance to antibiotics. Due to the low digestibility of zinc, high doses of ZnO in the feed leads to high zinc emission in feces of the livestock, thus causes the waste of resources and the environmental pollution ( 2 , 3 ). Many countries have phased out the use of colistin sulfate, olaquindox and high-dose ZnO as feed additives.…”
Section: Introductionmentioning
confidence: 99%